The Unity of Science Paradigm for Suistainable Education in The Disruption Era - Dwi Wulan Sari (Proceeding International Conference on Religion, Science and Education, 2023)
With the development of science towards modern civilization, education is faced with many problems that accompany it. Such as the separation between science and religion. The lack of implementation of the integration model of science and religion can lead to stagnancy and degradation of Sustainable education in Indonesia. The development of an increasingly global world civilization makes various problems complicated that cannot be solved with one discipline alone so the unity of science is needed. The concept of learning that integrates the value of science and religion in an era of disruption will create great changes in the ecosystem and the way of life. The era of disruption is believed to be able to improve the teaching process (Cyber System) by utilizing digital technology so that the inheritance of science can run continuously without the need for face-to-face. The purpose of this article is to analyze how the paradigm of unity of science plays a role in continuing education both adaptively and comprehensively in an era of disruption. The method used in this study is a descriptive qualitative method with a literature review. The results of the research analysis show that creating sustainable education requires good collaboration in religion and science to be able to solve challenges in the era of disruption. It does not dictate between science and Islam in scientific development and can correlate religious learning with science as the foundation of the era of disruption. Develop integration-interconnection or multidisciplinary, interdisciplinary, and transdisciplinary models at the institutional level and during learning so that it is expected to be applied by Islamic education with the principle of relevance and problem-solving in social life.